2014
DOI: 10.1308/003588414x14055925058634
|View full text |Cite
|
Sign up to set email alerts
|

Video assisted thoracoscopic thyroidectomy for retrosternal goitre

Abstract: INTRODUCTION Thyroidectomy for retrosternal goitre is usually carried out through a cervical incision. Around 4-12% of patients, however, require an extracervical approach, usually by sternotomy. Anatomically, the thyroid extends deep behind the great vessels in the pretracheal fascia. A sternotomy is therefore not only a substantial incision but this anterior approach is also not ideal for exposure. We report the use of video assisted thoracoscopic surgery (VATS) instead of a sternotomy or thoracotomy in conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…Manubriotomy is considered to be another safe alternative, which allows exposure of structures within the thoracic inlet although direct comparison of this technique against others has not been evaluated in terms of patient risk [12]. Newer techniques such as endoscope-assisted and video-assisted thoracoscopic thyroidectomy also provide options for minimally invasive surgical removal of RSG [15]. Further study of the success of these techniques is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Manubriotomy is considered to be another safe alternative, which allows exposure of structures within the thoracic inlet although direct comparison of this technique against others has not been evaluated in terms of patient risk [12]. Newer techniques such as endoscope-assisted and video-assisted thoracoscopic thyroidectomy also provide options for minimally invasive surgical removal of RSG [15]. Further study of the success of these techniques is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies have reported good results from using less invasive methods than open thoracic surgery, such as VATS (video-assisted thoracoscopic surgery). [29,30] …”
Section: Discussionmentioning
confidence: 99%
“…With these significant morbidity considerations in mind, they concluded that where anatomically possible, a trans-cervical approach should be used regardless of pathology [4] . Alternatively, there are reported video-assisted thoracoscopic approaches which may be of benefit in select patients where the anterior mediastinal space may be accessed [15] .…”
Section: Discussionmentioning
confidence: 99%